Tinjauan Pustaka: Potensi Aktivitas Antioksidan Spirulina sp Terhadap Penyakit-penyakit Metabolik dan Proses Degeneratif - Arya Patadan; Marina Astrid Rumawas; Susana Elya Sudrajat (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Free radicals are normal metabolites in the form of molecules of one or more unpaired electrons, so they are highly reactive and can cause cell damage and disrupt homeostasis. Depletion of antioxidants or accumulation of free radicals can cause oxidative stress, which plays a role in various disease processes such as inflammation, cancer, hemochromatosis, emphysema, high blood pressure to the aging process. Spirulina platensis is also known as blue-green filamentous algae because it is a colony-forming blue-green autotroph where columnar cells are arranged in columns to form twisted filaments resembling helices. C-Phycocyanin is one of the major groups of water-soluble and widely distributed phycobiliprotein in spirulina. The purpose of writing this literature review is to determine the potential antioxidant activity of Spirulina platensis against metabolic diseases and degenerative processes. This writing is in the form of a literature study by searching for data using two databases, Pudmed and Google Scholar. The keywords used are, Spirulina platensis, antioxidant activity, metabolic and degenerative diseases. After being selected based on inclusion and exclusion criteria, 21 references were obtained for review. Spirulina platensis has shown antioxidant, antidiabetic and antihypertensive effects in vitro and in vivo.